Correction: Insulative wood materials templated by wet foams. Issue 4 (2nd February 2023) - Ferreira, Elisa S.; Dobrzanski, Elizabeth; Tiwary, Praphulla; Agrawal, Prashant; Chen, Richard; Cranston, Emily D.
Abstract : Correction for 'Insulative wood materials templated by wet foams' by Elisa S. Ferreira et al., Mater. Adv., 2023, 4, 641–650, ; https://doi.org/10.1039/d2ma00852a .